Salt precipitation during CO2 storage—A review. (August 2016) - Miri, Rohaldin; Hellevang, Helge
Highlights: Review of recent studies on salt precipitation during CO2 storage. Lack of experimental data on injectivity alteration caused by salt precipitation leads to large uncertainty in studies. New physical understanding suggest that salt precipitation must be taken into account when evaluating saline aquifers for storage. Majority of numerical studies has dealt with the salt precipitation under simple and idealized conditions. Research on the mathematical modelling is the most demanding task. Abstract: This paper reviews the state-of-the-art knowledge gained from experimental and theoretical investigations on salt precipitation in the context of CO2 storage in saline aquifers. Included in this review are physical mechanisms, governing parameters, clogging models, and mitigation techniques. The approach is generally conceptual, and our aim is to specify how serious salt precipitation is for CO2 storage and whether its importance has been overlooked. Our review specifies some new physical understandings suggesting that salt precipitation must be taken into account when evaluating saline aquifers for storage. We also list unresolved areas which demand further experimental investigation and suggest some essential considerations with regard to numerical tools.